Factor completely, then place the factors in the proper location on the grid.
4x2+ 8xy - 60y2

Question

Asked 11/17/2014 10:17:11 PM

Updated 11/18/2014 11:13:50 PM

1 Answer/Comment

This conversation has been flagged as incorrect.

Flagged by janezeshun [11/18/2014 11:11:47 PM]

s

fontaine|Points 10|

Question

Asked 11/17/2014 10:17:11 PM

Updated 11/18/2014 11:13:50 PM

1 Answer/Comment

This conversation has been flagged as incorrect.

Flagged by janezeshun [11/18/2014 11:11:47 PM]

Rating

8

4x^2+ 8xy - 60y^2

= 4(x^2 + 2xy - 15y^2)

= 4(x + 5y)(x - 3y)

= 4(x^2 + 2xy - 15y^2)

= 4(x + 5y)(x - 3y)

Added 11/18/2014 11:13:50 PM

This answer has been confirmed as correct and helpful.

Factor this expression completely, then place the factors in the proper location on the grid.
x3y3 + z3

Question

Not Answered

Updated 11/18/2014 2:12:45 AM

1 Answer/Comment

Factor this expression completely, then place the factors in the proper location on the grid.
5x3 + 40y6

Question

Not Answered

Updated 11/18/2014 2:08:31 AM

1 Answer/Comment

Perform the indicated operation.
x3 x2
User: Perform the indicated operation.
(14x3y2z)4

Question

Updated 11/18/2014 2:05:47 AM

2 Answers/Comments

(14x^3y^2z)^4 = 38,416x^12y^8z^4

Added 11/18/2014 2:05:26 AM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [11/18/2014 2:32:52 AM]

Perform the indicated operation.
(3a2 - 7xy)(3a2 + 7xy)
**Weegy:** The answer is 9a^4-49x^2y^2. **User:** Perform the indicated operation.
(r + s)(r2 - rs + s2) **Weegy:** 3-3 = 0 **User:** Perform the indicated operation.
(2a2 - 8)(4a4 + 16a2 + 64)
**Weegy:** The answer for (2a2 - 8)(4a4 16a2 64) is 4096 a^6 (2 a^2-8). **User:** Factor this expression completely.
16x4 + 56x2 + 49
**Weegy:** 64, 112, 49 **User:** Factor this expression completely.
2x2 + 11x + 15
(More)

Question

Updated 11/18/2014 1:24:08 AM

5 Answers/Comments

(r + s)(r2 - rs + s2)

= r3 - r2s + rs2 + r2s - rs2 + s3

= r3 + s3

= r3 - r2s + rs2 + r2s - rs2 + s3

= r3 + s3

Added 11/18/2014 1:21:15 AM

This answer has been confirmed as correct and helpful.

2x2 + 11x + 15 = (2x + 5)(x + 3)

Added 11/18/2014 1:22:35 AM

This answer has been confirmed as correct and helpful.

16x^4 + 56x^2 + 49 = (4x^2+7)^2

Added 11/18/2014 1:23:36 AM

This answer has been confirmed as correct and helpful.

(2a2 - 8)(4a4 + 16a2 + 64) = 8a6 - 512

Added 11/18/2014 1:24:08 AM

This answer has been confirmed as correct and helpful.

Which are zeros of the following polynomial?
6x 2 - 11x - 10 = 0
x = 6, x = 10
x = ; x =
x = -2; x = 5
x = ; x =

Question

Updated 11/24/2014 12:49:26 AM

1 Answer/Comment

34,451,507

questions answered

S

L

1

1

1

1

1

1

1

1

1

1

1

1

1

1

1

1

1

P

1

L

P

1

Points 637 [Total 6510] Ratings 11 Comments 527 Invitations 0 Offline

There are no comments.